2016
DOI: 10.1017/s1355617716000138
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Atrophy in Adult Survivors of Childhood Cerebellar Tumor

Abstract: The results of the current study suggest that young age at diagnosis and radiation is associated with CB atrophy, which interacts with lesion size to impact both written and oral PS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Many survivors presented with poor processing speeds, leading to poorer physical and/or mental health, social functioning, and health‐related quality of life . Similarly, language and vocabulary issues were challenging .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many survivors presented with poor processing speeds, leading to poorer physical and/or mental health, social functioning, and health‐related quality of life . Similarly, language and vocabulary issues were challenging .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, language and vocabulary issues were challenging . Compared with matched healthy controls, brain tumour survivors scored significantly lower in verbal assessments …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocephalus, a common neurological condition in brain tumor survivors, results in increased intraventricular pressure, damage to periventricular white matter and possible axonal degeneration ( Krishnamurthy and Li, 2014 ). Surgical resection of the tumor beyond the tumor margin as often required causes a loss of brain tissue in areas of the brain that are in the same neural pathway but distal to the site of the lesion ( Ailion et al, 2016 ). Tractography studies in adult patients have found displacement and tumor infiltration in white matter tracts as a result of fast-growing tumors ( Nilsson et al, 2008 ; Wei et al, 2014 ) with persistent effects of thinning, interruptions and reductions in the tract size after surgery ( Lazar et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%